Combining the role of green finance and environmental sustainability on green economic growth: Evidence from G-20 economies. (May 2023) - Ma, Mengjuan; Zhu, Xiao; Liu, Meishan; Huang, Xiaodong
Abstract: Green finance and renewable energy are aimed at enhancing the world's economy and environmental sustainability. This study examines the link between green finance, renewable energy investment, green economic recovery, and environmental performance in G-20 countries. We employ a quantile regression model based on the 2010–2020 to estimate the effects of green economics and digital banking on environmental preservation. This study empirically demonstrated the integration of these variables. The pooled mean group estimation results imply that non-emerging countries and nations with more vital technologies or sustainability strategies may gain from environmental performance. Digital finance affects operating performance more than economies of scale according to the effect mechanism test. Green finance boosts energy-environmental performance more in regions with less-developed credit and capital markets. In developing countries and those with low levels of green finance, green financing facilitates green innovation. However, it negatively affects green product innovation in industrialised countries with high levels of green innovation or sustainability policies. The empirical findings have policy implications for developing nations to foster green innovation and improve environmental performance. Highlights: Green finance and environmental sustainability were examined. We employed quantile-on-quantile regression. Green finance boosts the environmental sustainability in G-20 economies. Green finance boost environmental performance in G-20 regions.